Model Konseptual Pendidikan Farmasi Berbasis Worldview Islam dan Tibb Nabawi - Ofa Suzanti Betha; Maemunah Sa'diyah; Budi Handrianto (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2026)
This study aimed to evaluate the effects of purified gambir (Uncaria gambir Roxb.), vitamin C, and their combination on AST levels in male mice subjected to maximal physical activity. Twenty-five male albino mice were randomly divided into five groups (n=5/group): normal control, maximal physical activity control, purified gambir 200 mg/kg body weight + maximal physical activity, vitamin C 65 mg/kg body weight + maximal physical activity, and a combination of purified gambir 100 mg/kg body weight and vitamin C 32.5 mg/kg body weight + maximal physical activity. Treatments were administered orally for 7 days. On day 8, maximal physical activity was induced by forced swimming for approximately 15 min. Serum AST levels were measured photometrically at 340 nm. Data were analyzed using the Shapiro-Wilk test, Levene’s test, Kruskal-Wallis test, and exploratory Mann-Whitney U test. The mean serum AST levels in Groups I, II, III, IV, and V were 141.4 ± 5.98, 146.6 ± 6.88, 122.6 ± 14.26, 124.8 ± 9.96, and 118.8 ± 6.46 IU/L, respectively. The Kruskal-Wallis test showed a significant overall difference among groups (p=0.007). Descriptively, the purified gambir, vitamin C, and combination groups showed lower AST levels than the maximal physical activity group. The combination group showed the lowest mean AST level; however, no significant difference was found between the combination group and the single-treatment groups in exploratory pairwise analysis. Purified gambir, vitamin C, and their combination were associated with lower serum AST levels in male mice subjected to maximal physical activity compared with the physical activity-only group. Although the combination treatment showed the lowest mean AST level, its statistical superiority over purified gambir alone or vitamin C alone was not demonstrated. These findings suggest a potential protective effect against exercise-associated tissue stress, although further studies using larger sample sizes and more specific biomarkers are needed.